Pendampingan Ekonomi Kreatif Bagi Komunitas Ibu Rumah Tangga - Rina Teriasi; Yolantya Widyasari; Jeffry Simson Supardi; Danella Merdiasi; Chris Apandie; Lelly Sepniwati (Universitas Pahlawan Tuanku Tambusai, 2022)
Community service activities in the Mandomai Village is intended to improve the community's economic level by providing assistance to the people in the Mandomai Village, by utilizing the assets they have such as the housewife community. The applied method is Asset Based Community Development (ABCD). This aims to help community members, especially housewives, to have a new perspective on life so as to create a conducive climate for perseverance, especially in building a business in the culinary field. Thus, the Mandomai community can maintain the continuity of family life and improve the family's economic welfare. For this reason, Creative Economy Assistance activities are programmed for housewives in Mandomai Village. This activity received a good response because it suits the needs and can provide new insights and skills or abilities in the home business field.